2017
DOI: 10.3390/su9101776
|View full text |Cite
|
Sign up to set email alerts
|

Bonus Point System for Refuse Classification and Sustainable Development: A Study in China

Abstract: Abstract:The rapid growth of household waste not only endangers the environment and people's health, but also limits social and economic development. The effective sorting and recycling of garbage can control this problem. Adopting a semi-quantitative case study method, our researchers investigated the effect of a bonus point system for refuse classification that improves the accuracy of refuse classification and the residents' environment awareness. In the system, residents will receive some gifts after sorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Although the survey data showed no impact of the educational level of farmers, as an important part of infrastructure construction, education should be vigorously developed, since cultivating high-quality talent is an important cornerstone of creating human capital for regional development. Besides, the introduction of Internet intelligent management mode would greatly reduce the management costs, being more convenient for residents [33].…”
Section: Proposed Strategiesmentioning
confidence: 99%
“…Although the survey data showed no impact of the educational level of farmers, as an important part of infrastructure construction, education should be vigorously developed, since cultivating high-quality talent is an important cornerstone of creating human capital for regional development. Besides, the introduction of Internet intelligent management mode would greatly reduce the management costs, being more convenient for residents [33].…”
Section: Proposed Strategiesmentioning
confidence: 99%
“…Lucia et al [ 12 ], Guo et al [ 13 ], Miafodzyeva et al [ 14 ], Convery et al [ 15 ] and Wu [ 16 ] claimed that residents’ household waste classification will be significantly affected by reward and punishment policies, and positive economic incentives are more easily accepted by residents. Wadehra et al [ 17 ] confirmed in the investigation of waste classification in India that the quality of the reward and punishment mechanism is closely related to the implementation effect of the classification policy, and a high-quality reward and punishment mechanism can strengthen the residents’ willingness to classify garbage and promote the residents to implement the behavior of waste classification.…”
Section: Research Hypothesismentioning
confidence: 99%
“…The application and examination of the measurement scales to festivals with other cultural or artistic themes in different countries would definitely help refine their validity and reliability. Last but not least, in light of the wide application of technology-assisted learning under various environmental education scenarios [47,48], understanding the effectiveness of visitor learning of compulsory waste sorting will be greatly leveraged by comparative analyses of the learning facilitated by host interpretations and by technology.…”
Section: Limitations and Future Researchmentioning
confidence: 99%